(untitled) (Journal of EAHIL, 2026)
Libraries play a central role in the well-being of young people, offering inclusive spaces where culture, relationships, and care intertwine. In a complex digital ecosystem, they become centers of cultural proximity capable of supporting imagination and health. Through reading, community groups, social prescription practices, and Health Humanities, libraries are becoming integrated infrastructures for young people and communities.